O pomiarze użyteczności ubezpieczeń - Mojsiewicz, Magdalena (On the Measuring of Utility of Insurance Policies, 2008)
The article presents the results of the utility function estimation for the potential consumers of the Polish insurers. The risks ordering was illustrated on the basis of 500 random chosen households in Poland. The study was carried out by TNS OBOP between July and August 2006. In the selected groups of the insurance products, the participants were questioned about declared policy premium protecting from the chosen risk. The aim of the article was to present the comparative analysis for each insurance group and the psychometric profile for selected preference target groups in terms of the sale of the households risk.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 269-278